Designing The Government Institution Performance Accountability System Implementation Using Soft Systems Methodology Approach, Study At The BMKG Indonesia - Achmad Supandi; Anni Arumsari Fitriany (Sean Institute, 2024)
His study aims to explore the factors that support or inhibit the implementation of the Government Institution Performance Accountability System (SAKIP) at the Meteorology, Climatology and Geophysics of the Republic of Indonesia (BMKG). This study uses the Soft Systems Methodology to ensure a systematic and comprehensive approach to this study. The findings show that compliance with laws and regulations, mutual agreement in compiling Government Agency Performance Accountability Reports (LAKIP), and strong leadership commitment are key factors supporting the implementation of SAKIP at BMKG. conversely, the use of ineffective performance management applications and inadequate organizational capacity are factors inhibiting the implementation of SAKIP at BMKG.